The destroyers : a novel - Bollen, Christopher, 1975- (Harper, an imprint of HarperCollinsPublishers, 2017)
"Arriving on the Greek island of Patmos broke and humiliated, Ian Bledsoe is fleeing the emotional and financial fallout from his father's death. His childhood friend Charlie--rich, exuberant, and basking in the success of his new venture on the island--could be his last hope. At first Patmos appears to be a dream--long sun-soaked days on Charlie's yacht and the reappearance of a girlfriend from Ian's past--and Charlie readily offers Ian the lifeline he so desperately needs. But, like Charlie himself, this beautiful island conceals a darkness beneath, and it isn't long before the dream begins to fragment. When Charlie suddenly vanishes, Ian finds himself caught up in deception after deception. As he grapples with the turmoil left in his friend's wake, he is reminded of an imaginary game called Destroyers they played as children--a game, he now realizes, they may have never stopped playing" -- provided by publisher.